2019
DOI: 10.18488/journal.136.2019.41.31.43
|View full text |Cite
|
Sign up to set email alerts
|

Drug Surrenderers and Crime Statistics During the Implementation of Project Double Barrel (PDB) in the Philippines

Abstract: Project double barrel (PDB) Crime statistics Drug surrenderers Index crime Non-index crime Illegal drugs Philippine national police (PNP) sorsogon.It is a fact that criminality related to illegal drugs is, indeed, a social problem which affects the growth of the nation and every aspect of community life. This study analyzed the profile of drug surrenderers and the crime statistics in the Province of Sorsogon during the implementation of Project Double Barrel in the Philippines. It was found out that most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Researchers may also instead opt to obtain informed consent and acquire research data verbally by default (e.g. interviews) as the likelihood of having illiterate participants in a study such as this is high (Dio et al, 2019; Pelegrino, 2022). Another limitation of the study was that it only measured psycho-social outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers may also instead opt to obtain informed consent and acquire research data verbally by default (e.g. interviews) as the likelihood of having illiterate participants in a study such as this is high (Dio et al, 2019; Pelegrino, 2022). Another limitation of the study was that it only measured psycho-social outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of education, most persons who use drugs have finished high school education or less. Studies in the Philippines have also reported that drug use is motivated by the need to stay awake or have more energy to work to support their families (Dio et al, 2019; Pelegrino, 2022). Other drivers of drug use include peer influence, unemployment and problems related to family and personal relationships (Estacio, 2018).…”
Section: Drug Use In the Philippinesmentioning
confidence: 99%
“…Without the trickledown effect, the rising of economic growth is meaningless. Dio et al (2019) analyzed the profile of drug surrenderers and the crime statistics in the Province of Sorsogon during the implementation of Project Double Barrel in the Philippines. It was found that most of the drug surrenderers are from the marginalized sectors belonging to informal workers, construction workers and jobless.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, Stealing and physical injury are the most prevalent crimes usually happens in the Philippines (see, Caba-ong et al, 2015). Moreover, the Municipality of Irosin as one among the municipalities with the highest number of recorded crime incidence has 33 or 39.4% solved cases in FY 2015 which also went higher in FY 2016 with 54.8% or 19 solved cases of crime incidents (Dio et al, 2019). To conclude it, Municipality of Irosin and Bulan are ranked higher in crime incidences, than other municipalities of Prieto Diaz, Sta.…”
Section: Population and Locale Of The Studymentioning
confidence: 99%
See 1 more Smart Citation